P03.08.B Proton Therapy and recurrent Lower Grade Glioma: clinical and radiological aspects, intraoperative findings and histo-pathological features. (5th September 2022) - Conti Nibali, M; Rossi, M; Sciortino, T; Gay, L; Lopci, E; Fernandes, B; Rudà, R; Bello, L
Abstract: Background: Radiation therapy (RT) plays a central role in management of central nervous system disease, in particular in the multimodality management of low(er) and high-grade CNS gliomas. New strategy that involved Proton Therapy (PT) have been experienced in the last years. No data are available about re-surgery of lesion irradiated with protons. Material and Methods: We reviewed our single Unit experience of re-surgery of Lower-Grade Glioma patients that received, in their neuro-oncological history, a treatment with PT. We collect clinical data, intra-operative findings, histopathological features and oncological and clinical outcome after surgery. Results: We collected three cases of young with an IDH1-mutated tumor that underwent to Proton Therapy (PT). In two cases PT was performed due to progression of disease, in one case as adjuvant therapy after first surgical treatment. In all cases we performed surgery within three years after PT. All patients complained drug resistant epilepsy after PT with symptom relief after surgery and one patient complained a spine fracture due to corticosteroids intake to control radionecrosis's symptoms after PT. In the pre-operative work-up all patient performed a 11-C-Methionin PET scan that revealed an increase of tracer uptake in the suspected area of tumor progression. In one case advanced MRI protocol with PWI was performed to further distinguish and sample area of pseudoprogression and tumor progression. In two patients area of gliosis and necrosis was find at the histological examination. Conclusion: Our experience, although limited to three case, provided a clinical and radiological example of the small cohort of patients that performed surgery after a Prothon Radiotherapy. Clinical presentation was heterogenous except a poor seizure control. Despite time elapsed since PT, areas of radionecrosis were found in the histopathological samples of 2/3 of patients. Moreover, we need to collect more data to draw a complete picture in this complex field.